Techno-economic Feasibility Analysis of Photovoltaic Charging Station for Electric Boats in Sabangko Island - Indradjaja, B. D.; Ramadhani, B.; Günther, Phil. M.; Gunawan, P. (Indonesian Journal of Energy, 2020)
Indonesia is the largest archipelago in the world. There are thousands of islands that are located far away from the grid that needs access to electricity. As a result, PV mini-grids have been installed in many remote islands. However, most of these PV mini-grids are under-utilized producing large amounts of unused excess energy. Since most of the inhabitants of these remote islands depend on fishing for their livelihoods, an idea was proposed to use excess energy from a PV mini-grid to power electric boats. This paper presents a techno-economic feasibility analysis of a PV charging station for electric boats using Sabangko Island in Makassar as an exemplary location. A detailed analysis of the existing system shows that there is enough excess energy to charge several boat batteries. The economic analysis shows that the LCOE of the project is quite low relative to other off-grid projects and the price of renting and charging a battery is still affordable.